“You’re Good as Long as You’re Silent”: Anti-Palestinian Racism in Schooling - Saleh, Muna; Saberi, Farid; Awwad, Nada (Critical Education, 2026)
In this article, we re/present our research alongside Palestinian Muslim students and families in Albert, focusing on research participants’ experiences of anti-Palestinian racism in k-12 schooling. To contextualize participants’ experiences, we explore literature around anti-Palestinian racism across Canadian and Israeli settler-colonial contexts. We elucidate two main narrative threads reverberating across research participants’ stories: participants experience(d) systemic anti-Palestinian racism in schools; yet they simultaneously engage(d) in education about Palestine in their homes and communities. Discussing ongoing anti-Palestinian racism in Canada, we conclude by offering several considerations and actions towards countering anti-Palestinian racism in Canadian schooling.